Variation in treatment modalities, costs and outcomes of rectal cancer patients in Poland - Herman, Krzysztof J.; Komorowski, Andrzej L.; Wysocki, Wojciech M.; Tabor, Jacek; Herman, Roman M.; Śliwczyński, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : To evaluate outcome, costs and treatment differences in rectal cancer patients between various regions in Poland. Material and methods : Data from the Polish National Health Fund of all patients with rectal cancer diagnosed and treated between 2005 and 2007 were analyzed. Overall, relative 5-year survival and the percentage of patients receiving chemotherapy, radiotherapy and surgery were analyzed. The possible influence of cost of treatment per patient and mean number of rectal cancer patients per surgical oncologist were analyzed as well. Results : In total 15,281 patients with rectal cancer were diagnosed and treated in Poland in 2005–2007 within the services of the National Health Fund. The overall, relative 5-year survival rate was 51.6%. Curative surgery was performed in 64.1% of patients. Radiotherapy and chemotherapy were used in 47.5% and 60.7% of patients, respectively. The mean cost of treatment of one rectal cancer patient was 32,800 PLN and there were 49.8 rectal cancer patients per specialist in surgical oncology. Important differences between regions were found in all these factors, but without a significant influence on survival. A correlation between numbers of patients per specialist in different voivodeships and survival rates was observed, as well as a correlation between percentage of surgical resection in voivodeships and survival rates (p = 0.07). Conclusions : Results of treatment of colorectal cancer in Poland improved significantly during the last decade. There exist however, important disparities between regions in terms of method of treatment, costs and outcomes.